Transactions Using the Cod (Cash on Delivery) Payment Method: Consumer Protection Legal Perspective - Aswal, Andi Azhim Fachreza (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The widespread use of e-commerce services by the public shows that buying and selling activities that were previously carried out conventionally have become activities that can be accessed only via smartphones, laptops/computers with an internet network. However, it is not uncommon for consumers to object because goods purchased using the cash on delivery or COD payment method do not match the order when they arrive at the delivery destination. This illustrates that one side of the consumer is the party that is seriously disadvantaged. Meanwhile, business actors still make a profit from selling the goods they make. Based on the problems above, the problem formulation is how to legally protect consumers for losses that can be suffered in transactions via COD and what measures can be taken by consumers for losses suffered in transactions via COD. This research method uses normative legal research. The approach used is the statutory and regulatory analysis approach which is used to answer the problems that have been previously formulated. The analysis technique is carried out qualitatively by describing the issues and then organizing them systematically and connecting them with the legal materials that have been found. Cash on Delivery (COD) means pay on delivery is a payment method that is in great demand in e-commerce. As the name suggests, this payment method allows buyers to make payments in cash when the order arrives at the destination address. Trading by e-commerce actually has a legal basis for ordinary trade. Or in other words, e-commerce is conventional trade that is special because the role of media and electronic devices is very dominant. Transactions using the COD payment method were initially present to facilitate online buying and selling transactions. However, this mechanism also has the potential to cause significant losses for consumers. Enforcement of consumer rights is a necessity in order to ensure legal certainty to provide protection to consumers, including in transactions that use the COD payment method as regulated in Article 4 of the Consumer Protection Law. There are various reasons for goods being returned by consumers who have used COD payments such as products. damaged, non-functioning products, insufficient products, incomplete orders, inappropriate products, and counterfeit products. For disputes that arise due to the COD system, there is a method that has been determined by each marketplace to submit an objection or request a return of goods to the business actor by attaching proof that the goods received do not meet consumer expectations. Meanwhile, consumers who feel their rights have been violated can complain and process their case legally at the Consumer Dispute Settlement Agency (BPSK) or through court.